PROSTATE VAPORIZATION BY DIODE LASER FOR PATIENTS WITH BENIGN PROSTATIC ENLARGEMENT - Mahdi Ali, Falah; Obaid, Ahmed Ali (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study were to study the efficacy of diode laser prostatectomy in patients infected with benign prostatic enlargement. Methods: A total of 62 men were included in our prospective clinical study from August 2017 to January 2018. The size of their prostates (ml) was ranged from 38 to 65, digital rectal examination for all patients was revealed the features of benign prostatic enlargement, prostate-specific antigen was ranged from 0.3 to 14 ng/ml, underwent laser prostatectomy (Diode laser). Results: The study included 62 men with 67.82±7.57 years. After the operation, the median maximum flow rate (Qmax) was increased 11–22 ml/s and the increment was highly significant (p<0.001), and median international prostate symptom score was highly significantly reduced from 19 to 10 (p<0.001). In addition, median residual volume was highly significantly reduced from 169.5 to 77 ml (p<0.001). Mean duration of operation was 67.82±7.57 min. The duration of catheterization with a mean of 1.16±0.45 days. Most patients required only 1 day of hospital stay postoperatively. No one developed post-operative bleeding, erectile dysfunction was reported in a single patient (1.6%), urinary incontinence in one patient (1.6%), and urinary tract infection was the most frequent post-operative complication being reported in 11.3%. Conclusion: Diode laser for the treatment of prostate is easily applicable, cheap and provides good ablation with low morbidity.